1983
DOI: 10.1097/00000658-198303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Hepatic-Aid and a Casein Modular Diet on Enceph-alopathy, Plasma Amino Acids, and Nitrogen Balance in Cirrhotic Patients

Abstract: Hepatic-Aid is purported to ameliorate encephalopathy and promote positive nitrogen balance in protein-intolerant, cirrhotic patients by correcting their imbalanced amino acid profile. This study evaluated Hepatic-Acid by comparing a 50-g Casein diet with an identical diet with 20-g Casein/30-g Hepatic-Aid per day in a cross-over study. Four patients with biopsy-proven stable cirrhosis, encephalopathy, and under-nutrition were studied. Each study period included three days of equilibration and eight days of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…In our previous study observing diurnal variation of plasma amino acid levels following the intake of the nutrient-mixture-supplemented diet, low plasma BCAA levels in a cirrhotic patient rose to normal during the entire 24-h period (7). In the report of McGhee et al (8) concerning the effects of Hepatic-Aid, a diet containing reduced AAA and increased BCAA, on plasma amino acid con centrations, they also observed the elevation of BCAA/AAA molar ratio attained by reduction in tyrosine and phenylalanine rather than by increase of BCAA. When the BCAA-supplemented diet was fed to cirrhotic patients (3), fasting plasma BCAA levels were increased and the BCAA/AAA molar ratios elevated, though AAA levels were not changed.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study observing diurnal variation of plasma amino acid levels following the intake of the nutrient-mixture-supplemented diet, low plasma BCAA levels in a cirrhotic patient rose to normal during the entire 24-h period (7). In the report of McGhee et al (8) concerning the effects of Hepatic-Aid, a diet containing reduced AAA and increased BCAA, on plasma amino acid con centrations, they also observed the elevation of BCAA/AAA molar ratio attained by reduction in tyrosine and phenylalanine rather than by increase of BCAA. When the BCAA-supplemented diet was fed to cirrhotic patients (3), fasting plasma BCAA levels were increased and the BCAA/AAA molar ratios elevated, though AAA levels were not changed.…”
Section: Discussionmentioning
confidence: 89%
“…In cirrhotic patients, the nitrogen balance with diets enriched with free BCAA has been found to be improved or unchanged with respect to that obtained with diet C. McGhee et al [25] and Christie et al [30] did not find a significant improvement in nitrogen balance between a casein diet and one enriched with free BCAA. In contrast, Egberts et al [7] and Marchesini et al [27] obtained a better nitrogen balance with diets enriched with free BCAA than with diets enriched with casein.…”
Section: Discussionmentioning
confidence: 94%
“…A higher BCAA/AAA ratio in plasma of animals on diet M than on diet H was unexpected because the latter diet presented a ten times higher BCAA/AAA ratio with respect to the BCAA-modified protein (table 4). McGhee et al [25] and Okita et al [26] reported that the elevation of the plasma BCAA/AAA ratio was attributable to the reduction of the Tyr and Phe levels rather than to an increase in the BCAA concentration, when Hepatic Aid and other nutrient-mixtures (with free BCAA) were fed to cirrhotics. In the case of our diet M, in addition to plasma Tyr and Phe levels comparable to diet H, the plasma BCAA levels were increased.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that long-term oral BCAA supplementation (about 0.25 g/kg) both exerts nutritional benefits and reduces the recurrence rates or symptoms of hepatic encephalopathy in patients with cirrhosis [59]. However, the currently available studies are often controversial [58]: an initial RCT including 37 cirrhotic patients reported that BCAA supplementation was superior to conventional protein supplements in improving hepatic encephalopathy [59], whilst two other RCTs failed to confirm these findings [60,61], even if they had a small sample size (eight and four patients only, respectively) and the BCAAs regimen was short-term (11-12 days). More recently, two RCTs including larger cohorts (174 and 646 patients, respectively) focused on the long-term use of BCAAs (1-2 years) among patients with alcoholic cirrhosis; both studies reported a decreased morbidity and mortality and an improved quality of life in the group receiving BCAAs [62,63].…”
Section: Dietary Interventionsmentioning
confidence: 99%